ICT Intentions and Digital Abilities of Future Labor Market Entrants in Finland - Kaarakainen, Meri-Tuulia (Nordic Journal of Working Life Studies, 2019)
Daily lives of citizens in current societies have changed with the spread of digital technologies, online services, and digital communication. Alongside this, the information and communication technology (ICT) labor force is expected to grow massively over the next years, requiring increased number of applicants for digital education and sufficient digital skills from every labor market entrant. This study examines the digital abilities of Finnish upper secondary school students (N = 3206) and the students’ intentions to study/work in the ICT field in the future. The results highlight a dissonance between the growth expectations and the popularity of the ICT field among young Finns. The students’ future intentions are also strongly gendered; for about 9% of males, but only about 1% of females in secondary education are planning to apply in the ICT field in the future. The students’ ICT intentions were predicted most strongly by being a male and possessing strong technical abilities